2011
DOI: 10.1186/1471-244x-11-186
|View full text |Cite
|
Sign up to set email alerts
|

Differences between patients' and clinicians' report of sleep disturbance: a field study in mental health care in Norway

Abstract: BackgroundThe aims of the study was to assess the prevalence of diagnosed insomnia and the agreement between patient- and clinician-reported sleep disturbance and use of prescribed hypnotic medication in patients in treatment for mental disorders.MethodsWe used three cross-sectional, multicenter data-sets from 2002, 2005, and 2008. Data-set 1 included diagnostic codes from 93% of all patients receiving treatment in mental health care in Norway (N = 40261). Data-sets 2 (N = 1065) and 3 (N = 1181) included diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The positive predictive value of clinicians’ evaluations of patients sleep disturbance (i.e. the probability that subjects clinically diagnosed truly have insomnia disorder) has been reported to be as low as 53% (Kallestad et al ., ). Qualitative studies have found that GPs wanted more training and tools to assess and manage insomnia better (Davy et al ., ; Dyas et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The positive predictive value of clinicians’ evaluations of patients sleep disturbance (i.e. the probability that subjects clinically diagnosed truly have insomnia disorder) has been reported to be as low as 53% (Kallestad et al ., ). Qualitative studies have found that GPs wanted more training and tools to assess and manage insomnia better (Davy et al ., ; Dyas et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Insomnia can be defined as the subjective experience of disturbed or non-restorative sleep that gives rise to daytime impairment despite adequate opportunity and circumstances for sleep (4,5). Despite its high prevalence, insomnia is often overlooked in clinical settings (6), and it is underdiagnosed in patients with CFS (7).…”
Section: Introductionmentioning
confidence: 99%
“…Primary insomnia (PI) (American Psychiatric Association, 2000) is a common comorbidity to anxiety as well as mood disorders (Cox & Olatunji, 2016). Insomnia is associated with lower quality of life, higher symptom severity, higher disorder severity, lower levels of functioning, and less benefit from treatment even when controlling for age, gender, time in treatment, type of care and the presence of any primary mental disorder (Kallestad, Hansen, B., Langsrud et al, 2011). Obsessive compulsive disorder (American Psychiatric Association, 2013) is regarded as one of the most disabling mental disorders (Murray & Lopez, 1996), and as a rule of thumb 35% to 40% of patients do not respond to recommended exposure-based cognitive behavioural treatments (Skapinakis, Caldwell, Hollingworth et al, 2016;€ Ost, Havnen, Hansen & Kvale, 2015).…”
Section: Introductionmentioning
confidence: 99%